Determinants of CO2 Emissions in Emerging Markets: An Empirical Evidence from MINT Economies - Tomiwa Sunday Adebayo; Ayobamiji Abraham Awosusi; Ibrahim Adeshola (International Journal of Renewable Energy Development, 2020)
CO2 emission is one the major contributor to climate change that the top CO2 emitting countries are always trying to mitigate.  In an attempt to fill the gap in energy and environmental literature, this study explores the interaction between economic growth, energy usage, trade and urbanization on CO2 emission for MINT economies using the time coverage from 1980 to 2018, providing new perspectives into the literature by employing panel data analysis. Aiming to create robust outcomes, this paper deployed both conventional and modern econometric techniques. The panel co-integration test revealed evidence of the co-integration between CO2 and its determinants in the MINT economies. In order to explore the linkages between CO2 and its determinants, the ARDL PMG model was utilized in MINT economies. Findings based on the ARDL PMG reveals; (i) positive interconnection between CO2 emissions and energy usage; (ii) no significant link was found between CO2 and economic growth; (iii) urbanization influence CO2 positively while a negative link was found between CO2 and trade. Furthermore, the Dumitrescu-Hurlin Causality test revealed; (i) uni-directional causality from CO2 to urbanization; (ii) GDP growth cause CO2 while CO2 causes energy usage. Based on these findings, recommendations were put forward.